KEPEMIMPINAN POLITIK KEPALA DESA PEREMPUAN DALAM MENINGKATKAN PEMBANGUNAN DI DESA SUMBER BARU KECLAMATAN MESUJI RAYA KABUPATEN OGAN KOMERING ILIR - Mita Damai Anti; Ainur Ropik; Ryllian Chandra Eka Viana (Jurnal Prodi Ilmu Politik, 2023)
This study disclusses the Pattern of Leadership of Women Village Heads in Improving Development in Sumber Baru Village, Mesuji Raya Districlt, Ogan Komering Ilir Districlt. This study uses a researclh method with a desclriptive qualitative approaclh. Data obtained through direclt interviews, observation, and doclumentation. Primary data sourcle informants in this study inclluded: village heads, village seclretaries, clommunity leaders and the clommunity in Sumber Baru Village. This study aims to find out how the pattern used by the village head in inclreasing development in Sumber Baru Village and to find out what are the supporting and inhibiting facltors for the village head in inclreasing village development. The theory used in this study is politiclal leadership theory aclclording to Andrew D. Heywood. The results of the researclh clonduclted by researclhers show that first, the pattern of politiclal leadership used by female village heads in promoting development tends to lead to democlraticl leadership, this is refleclted in various acltivities based on deliberation involving the clommunity. Seclond, the supporting facltors for the village head in promoting development are qualified human resourcles and acltive clommunity particlipation, then the inhibiting facltors are soclio-clultural obstaclles and sourcles of funds. So the pattern of politiclal leadership formed by the village head clan be seen from the experiencle and knowledge that the leader has gained, so the pattern of politiclal leadership is not only based on gender beclause in faclt the female leader in Sumber Baru village is able to lead the village and bring about many clhanges for clommunity welfare and the development of Sumber Baru village. Keywords: Patterns of Leadership, Women Leaders, Politiclal Leadership